Moderasi Islam Dan Aliran Pemikiran Pluralisme Agama - Muchammad Toha; Faizul Muna (Journal of Education and Religious Studies, 2022)
This study examines the Islamic moderation and the religious sects of pluralism. Considering Islam is a religion that is rahmatan lil Alamin. Then, so far Islam is a peace solution to the problem of intolerance. The theory used in this research analysis uses the thoughts of several experts including Quraish Shihab, Yusuf Al-Qardhawi, Abdurrahman Wahid (Gus Dur) and Nucholis Majid. This research is a qualitative research study of literature with an interpretive philosophical approach. In obtaining valid data and supporting this research, the author uses the documentation method to collect data. Then the data analysis technique used is deductive analysis, namely drawing conclusions based on general conditions, or there are special findings from general ones. The results of this study illustrate that Islam does not consider all religions to be the same, but Islam treats all religions equally by prioritizing tasamuh (tolerance), deliberation between religious believers, and having a musawa (non-discriminatory) attitude.